Kesalahan Penggunaan Keigo dalam Drama Nihonjin No Shiranai Nihongo - Nani Sunarni; Hilda Dian Estherina (Jurnal Bahasa Jepang Taiyou, 2019)
This study aims to describe language errors in honorific between native speakers (Japanese) and non native speakers (foreign students). This research uses a drama series called Nihonjin No Shiranai Nihongo (2010) as data source. The research applies analytical descriptive method to the dialogue discourses used as the data. It starts from data collecting process to be analyzed later based on the theory of language errors in the view of Yoshikawa (1997) and Error Analyis of Norish (1989). Based on the results of the analysis, it is identified that language errors occur due to lack of language understanding, error in Japanese honorifics. This research is theoretically very useful in adding references for the study of language errors and can practically be used as a basic for learning Japanese, especially learning Kaiwa.